Investigating the Effect of Atorvastatin in Preventing Ventilator Associated Pneumonia among Patients with Cerebral Ischemia Hospitalized in ICU in Imam Khomeini Hospital in Urmia City - Mohammad Reza Amiri-Nikpour (Journal of Global Pharma Technology, 2017)
Introduction:  ventilator associated pneumonia is one of the main reasons of death in patients under ventilator, especially those with impaired consciousness hospitalized in intensive care unit (ICU). Having anti-apoptotic, antioxidant, and immunomodulatory effects, atorvastatin can be effective in preventing pneumonia in patients with stroke who are under ventilator, while it is also prescribed to reduce cholesterol and accelerate recovery process in ischemia cases. The present study aims at investigating the preventive effects of atorvastatin on ventilator associated pneumonia among patients who suffer from stroke and are under the ventilator. Methodologies in the present study, 60 patients hospitalized in ICU unit under ventilator following an ischemic attack were divided to two groups of 30. The treatment group received a daily 40-mg dose of atorvastatin, while the control group didn’t. Then the occurrence of pneumonia was extracted for both groups during at least 14days of hospitalization, and the results were analyzed using SPSS20 software. Results the results of the study indicated that the amount of occurrence of pneumonia among patients treated by 40 mg atorvastatin was significantly lower than the patients in control group. Therefore prescribing daily 40 mg atorvastatin for the patients with ischemia in ICU unit who are incubated and are under mechanical ventilation would reduce ventilator associated pneumonia significantly. Conclusion atorvastatin has a significant reducing effect on occurrence of ventilator associated pneumonia in patients suffering from ischemic stroke in ICU unit, who are incubated and under mechanical ventilation, which will be proved clinically in the present study. Keywords: ventilator associated pneumonia, Cerebral ischemia, Atorvastatin.